Processing linguistic variation: challenges of building a comprehensive model for acquisition, diversity and comprehension (Revista de Estudos da Linguagem, 2024)
The study of the processing of linguistic variation is an interdisciplinary enterprise involving sociolinguistics, psycholinguistics and cognitive neuroscience. In order to contribute to descriptive and explanatory accounts regarding the processing and acquisition of variable input, considering the effects of external social pressure, this thematic volume presents 14 papers. The studies contribute to observational and experimental approaches exploring a variety of topics: morphosyntactic phenomena, such as verbal and nominal agreement, grammatical gender inflection, grammatical imperative and relative clauses, as well phenomena at the level of social conscience and linguistic ideologies regarding taboo, prejudice and attitudes towards, especially, minority languages. The results of these studies show the way to broaden existing methodological-theoretic approaches, especially those that seek to reconcile the strictly controlled nature of experimental paradigms and stimuli with the observer’s paradox as defined by sociolinguistics. This endeavor is complex and requires overcoming technological limitations and the current difficulty of theoretical models in dealing with language variability and structure.